T1 Mapping in Characterizing Myocardial Disease: A Comprehensive Review. Issue 2 (8th July 2016) - Puntmann, Valentina O.; Peker, Elif; Chandrashekhar, Y.; Nagel, Eike
Abstract : Cardiovascular magnetic resonance provides insights into myocardial structure and function noninvasively, with high diagnostic accuracy and without ionizing radiation. Myocardial tissue characterization in particular gives cardiovascular magnetic resonance a prime role among all the noninvasive cardiovascular investigations. Late gadolinium enhancement imaging is an established method for visualizing replacement scar, providing diagnostic and prognostic information in a variety of cardiac conditions. Late gadolinium enhancement, however, relies on the regional segregation of tissue characteristics to generate the imaging contrast. Thus, myocardial pathology that is diffuse in nature and affecting the myocardium in a rather uniform and global distribution is not well visualized with late gadolinium enhancement. Examples include diffuse myocardial inflammation, fibrosis, hypertrophy, and infiltration. T1 mapping is a novel technique allowing to diagnose these diffuse conditions by measurement of T1 values, which directly correspond to variation in intrinsic myocardial tissue properties. In addition to providing clinically meaningful indices, T1-mapping measurements also allow for an estimation of extracellular space by calculation of extracellular volume fraction. Multiple lines of evidence suggest a central role for T1 mapping in detection of diffuse myocardial disease in early disease stages and complements late gadolinium enhancement in visualization of the regional changes in common advanced myocardial disease. As a quantifiable measure, it may allow grading of disease activity, monitoring progress, and guiding treatment, potentially as a fast contrast-free clinical application. We present an overview of clinically relevant technical aspects of acquisition and processing, and the current state of art and evidence, supporting its clinical use.